Anti-inflammatory Activity of Lemon Pepper Nanoemulsion on Carrageenan-Induced Male Wistar Rat - Linda Chiuman; Dwi Putri Agita Sebayang; Veranyca Chiuman; Suhartomi Suhartomi (Jurnal Penelitian Pendidikan IPA, 2023)
Lemon pepper does not only have a unique taste but also has some active compounds, which has anti-inflammatory activity. This study intended to investigate the anti-inflammatory effect of lemon pepper nanoemulsion on carrageenan-induced Wistar rats. This experimental study used Twenty-five male Wistar rats that were grouped into five different groups, including control, standard, lemon pepper nanoemulsion dose of 25, 50, and 75 mg/ kgBW. Initially, all rats received air injection in the back area for 5 days to form an air pouch. After that, all rats were injected with 1% carrageenan solution, and received treatment based on the groups for 48 hours via oral route. Then, it counted the number of white blood cells by Giemsa Stain that was expressed as a number of cells per High Power Field (HPF). The increasing of Lemon pepper nanoemulsion dose significantly decreased the number of leucocytes in the carrageenan aspiration after 48 hours of treatment (P-Value < 0.001). The lowest number of leucocytes was found in the Lemon Pepper Nanoemulsion dose of 75 mg/kgBW (2.40 leukocytes per HPF). Hence, it can be deducted that the lemon pepper nanoemulsion has an anti-inflammatory effect, especially at a dose of 50-75 mg/kgBW.